On the influence of the geometrical irregularities in the mechanical response of Wire-and-Arc Additively Manufactured planar elements. (March 2021) - Laghi, Vittoria; Palermo, Michele; Gasparini, Giada; Girelli, Valentina Alena; Trombetti, Tomaso
Abstract: The use of Additive Manufacturing (AM) technologies in the construction industry is still at its pioneering stage. The first investigations indicate that, among actually available metal 3D-printing strategies, Wire-and-Arc Additive Manufacturing (WAAM) process appears to be the most suitable for realizing large-scale steel structures. Nonetheless, the limited knowledge of the mechanical response of WAAM-produced alloys requires further experimental work for a reliable evaluation of the structural behavior of WAAM structural members. One specific issue which still needs to be fully investigated is the peculiar geometrical irregularity resulting from WAAM process that could have non-negligible effects on the mechanical behavior, such as anisotropy and non-homogeneous stress-strain fields. The present work explores the influence of the inherent geometrical irregularities of planar 308LSi stainless steel WAAM specimens on the tensile response. For this purpose, detailed geometrical characterization of the external surface of WAAM specimens was carried out with 3D scanning techniques and random field theory. Different sets of specimens were subjected to tensile tests to evaluate the influence of surface finishing (machined vs. as-built), orientation (with respect to the printing layers) and cooling strategy on the key mechanical parameters. The whole strain field was then studied in detail through Digital Image Correlation (DIC) monitoring technique. Key findings are given in terms of geometrical characterization of surface roughness and thickness variability, as well as a quantitative assessment of the influence of geometrical irregularities on the main mechanical parameters. The material response reveals a significant anisotropy related to a marked crystallographic micro-texture. The geometrical irregularities negatively impact some of the mechanical parameters of the as-built material, suggesting further considerations for practical structural design applications. Graphical abstract: Unlabelled Image Highlights: Wire-and-Arc Additively Manufactured (WAAM) elements are characterized by inherent geometrical irregularities. The thickness distribution of WAAM specimens is studied through random field theory. Specimen-to-specimen effective thickness variability is also quantified. The effect of the geometrical irregularities on the mechanical response of WAAM specimens is studied through tensile tests. The specimens considered are compared in terms of surface finishing, orientation from printing layers and cooling strategy.